Regulation of cell proliferation and cell density by the inorganic phosphate transporter PiT1 - Byskov Kristina; Jensen Nina; Kongsfelt Iben; Wielsøe Maria; Pedersen Lasse; Haldrup Christa; Pedersen Lene (Cell Division, 2012)
Abstact Background The inorganic phosphate (Pi) transporter, PiT1 (SLC20A1), is ubiquitously expressed in mammalian cells. It has previously been shown that down-regulation of PiT1 severely impaired the proliferation of two transformed human cells lines, HepG2 and HeLa, and the tumorigenicity of HeLa cells in nude mice. Moreover, PiT1 knock-out mice do not survive past E12.5 and from E10.5, the embryos were found to be growth-retarded and showed reduced proliferation of liver cells. Isolated mouse embryonic fibroblasts with knocked out as well as reduced PiT1 expression levels also exhibited impaired proliferation. Together these results suggest that a certain level of PiT1 is important for proliferation. We have here investigated the role of PiT1 in regulation of cell proliferation using two strictly density-inhibited cells lines, the murine MC3T3-E1 and NIH3T3 cells. Results We found that knock-down of PiT1 in MC3T3-E1 cells led to impaired proliferation supporting that at least a certain level of PiT1 is important for wildtype level of proliferation. We, however, also observed that MC3T3-E1 and NIH3T3 cells themselves regulate their endogenous PiT1 mRNA levels with lower levels in general correlating with decreased proliferation/increased cell density. Moreover, over-expression of human PiT1 led to increased proliferation of both MC3T3-E1 and NIH3T3 cultures and resulted in higher cell densities in cultures of these two strictly density-inhibited cell lines. In addition, when we transformed NIH3T3 cells by cultivation in fetal bovine serum, cells over-expressing human PiT1 formed more colonies in soft agar than control cells. Conclusions We conclude that not only is a certain level of PiT1 necessary for normal cell division as suggested by previously published studies, rather the cellular PiT1 level is involved in regulating cell proliferation and cell density and an increased PiT1 expression can indeed make NIH3T3 cells more sensitive to transformation. We have thus provided the first evidence for that expression of the type III Pi transporter, PiT1, above the endogenous level can drive cell proliferation and overrule cell density constraints, and the results bridge previous observations showing that a certain PiT1 level is important for regulating normal embryonic growth/development and for tumorigenicity of HeLa cells.